International business in conflict zones: the case of MTN - Omoola, Sodiq; Ahmad, Abubakar Aminu (Conflict Studies Center, College of Political, Administrative and Communication Sciences at Babeș-Bolyai University of Cluj-Napoca, Romania., 2024)
: It is not uncommon for multinational companies to establish subsidiaries outside their home countries, especially in developing regions to tap into emerging markets. It is however a different situation when multinationals establish businesses in unstable and violence-affected regions to take advantage of the local market structure that has suffered a hit by the continuous conflict. However, running a business in such regions may lead to distortion of the administration of these firms due to the violence which may destroy infrastructure and harm employees. Many firms are discouraged from investing in conflict zones because of the exposure to insecurity and violence. This paper adopts a case study and case analysis approach with an in-depth focus on the operation of a specific company and its operations in two conflict zones which resulted in distinct outcomes. In addition, a review of existing literature on the establishment and operation of a business in conflict zones was carried out to effectively examine the challenges of litigation and conflict resolution involving MTN Group as a corporate entity in Afghanistan and Northeastern Nigeria and the impact on the business operations in the respective regions.